The flu far and near: Comparing the 1918 and 2009 pandemics - Alvarez, Adriana; Carbonetti, Adrián; Carrillo, Ana María; Filho, Claudio Bertolli [UNESP]; de Souza, Christiane Maria Cruz; Bertucci, Liane Maria; Azevedo, Nara (My University, 2009)
In this debate, Latin American historians compare the 1918-1919 flu pandemic with the one sweeping the continent in 2009, focusing especially on the experiences in Mexico, Argentina, and Brazil. They analyze the strategies adopted on both occasions, above all isolation measures, port and airport surveillance, and urban interventions. Comparisons are drawn between the actions of federal and local governments, positions taken by doctors and the media, and people's behavior, particularly regarding fear and death. The debaters also analyze the performance of assistance structures, the treatment and prevention measures recommended by public health agencies and private groups with a vested interest in drug sales, and popular and home remedies. The debate extends to how the 1918 experience has influenced the evaluation of today's crisis and what legacy it may leave behind.
Keywords: History of diseases; Influenza A (H1N1); Latin america; Pandemics; Spanish flu